The Emerging Roles of Circular RNAs in the Chemoresistance of Gastrointestinal Cancer - Wang, Man; Yu, Fei; Zhang, Yuan; Zhang, Lei; Chang, Wenguang; Wang, Kun (Frontiers in Cell and Developmental Biology, 2022)
Gastrointestinal (GI) cancer represents a major global health problem due to its aggressive characteristics and poor prognosis. Despite the progress achieved in the development of treatment regimens, the clinical outcomes and therapeutic responses of patients with GI cancer remain unsatisfactory. Chemoresistance arising throughout the clinical intervention is undoubtedly a critical barrier for the successful treatment of GI cancer. However, the precise mechanisms associated with chemoresistance in GI cancer remain unclear. In the past decade, accumulating evidence has indicated that circular RNAs (circRNAs) play a key role in regulating cancer progression and chemoresistance. Notably, circRNAs function as molecular sponges that sequester microRNAs (miRNAs) and/or proteins, and thus indirectly control the expression of specific genes, which eventually promote or suppress drug resistance in GI cancer. Therefore, circRNAs may represent potential therapeutic targets for overcoming drug resistance in patients with GI cancer. This review comprehensively summarizes the regulatory roles of circRNAs in the development of chemoresistance in different GI cancers, including colorectal cancer, gastric cancer and esophageal cancer, as well as deciphers the underlying mechanisms and key molecules involved. Increasing knowledge of the important functions of circRNAs underlying drug resistance will provide new opportunities for developing efficacious therapeutic strategies against GI cancer.